1998
DOI: 10.1021/ac9803481
|View full text |Cite
|
Sign up to set email alerts
|

A Parallel Multiharmonic Frequency-Domain Fluorometer for Measuring Excited-State Decay Kinetics Following One-, Two-, or Three-Photon Excitation

Abstract: We report on the performance of a new, multiharmonic frequency-domain instrument that uses the high harmonic content of a passively mode-locked, pulse-picked femto-second Ti-sapphire laser as the excitation source for the determination of one-, two-, or three-photon excited time-resolved fluorescence anisotropy and intensity decay kinetics. In operation, the new instrument can provide a complete frequency-domain data set at 100 modulation frequencies in less than 1 min. The new instrument exhibits 5-10-ps meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 78 publications
(104 reference statements)
5
26
0
Order By: Relevance
“…The concentration dependent quenching follows a Stern-Volmer model of bimolecular quenching (29,30). The relationship between the observed fluorescent lifetime, f , and the quencher concentration, [Q], is given by (15) where k q is the bimolecular rate constant for quenching, [Q] is the concentration of quencher, and f o is the fluorescent lifetime in the absence of quencher.…”
Section: Dynamic Quenching Of Rhodamine 6g By Iodidementioning
confidence: 99%
See 2 more Smart Citations
“…The concentration dependent quenching follows a Stern-Volmer model of bimolecular quenching (29,30). The relationship between the observed fluorescent lifetime, f , and the quencher concentration, [Q], is given by (15) where k q is the bimolecular rate constant for quenching, [Q] is the concentration of quencher, and f o is the fluorescent lifetime in the absence of quencher.…”
Section: Dynamic Quenching Of Rhodamine 6g By Iodidementioning
confidence: 99%
“…These wavelengths were chosen to match the typical spectral ranges of fluorophores commonly used in biological experiments, particularly those utilizing wild type and mutant forms of the green fluorescent protein (GFP). We used rhodamine 6G as a reference because of extensive prior work indicating that the dye has a single-component lifetime (29,30,33) and a linear Stern-Volmer behavior (29,30). We encountered difficulties with fluorescein standard solutions because of lifetime inconsistencies attributed to photobleaching artifacts.…”
Section: Acquisition and Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] Over the past decade, sol-gel-processed thin films have been used in concert with a number of Ru(II) tris α-diimine dopants to produce luminescence-based sensors for O 2 quantification, with potential clinical, environmental, and process control applications. [8][9][10][11] Particularly promising among the Ru(II) diimine series is tris(4,7'-diphenyl-1,10'-phenanthroline) Ru(II) ([Ru(dpp) 3 ] 2+ ) which exhibits a high luminescence quantum yield, a long-lived excited-state luminescence lifetime, good photostability, large emission Stokes shift, and high molar absorptivity in the blue-green spectral region. [12][13][14][15][16][17] The photophysics and photochemistry of Ru(II) diimine quenching by O 2 is also well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Quenching studies have been used to control observed fluorescence lifetimes (28,29), in fundamental studies (30), and to assist in the resolution of mixtures (31). Quenching has been used to assay for hydrolyzing enzymes (32) and in biophysical studies to obtain information about the environment in which a fluorophore is located in a protein (33).…”
mentioning
confidence: 99%